Participatory Field Studies during the Covid-19 Pandemic: A Study in North Ampenan: Studi Lapangan Partisipatif Selama Pandemi Covid-19: Studi di Ampenan Utara - Wahyuni Arafani; Ayu Qurniasih; Siti Aminah; Nurlaili Agustina; Hamid Muhammad Gassir; Istiqomah; Husnul Hotimah; Daeng Omy Husnusyifa; Indah Fadlina; Vini Arfina Zakiatul Yaqin; Rini Anggraeni; Sahrul; Barry Sanjaya; Wulan; Fauzia Nindita Maulida; Putri Ramadani; Windy Putri Mirani (Jurnal Pengabdian Masyarakat Tropis Indonesia, 2025)
The Participatory Field Study Program or KKP-DR was implemented as an adaptive response to the Covid-19 pandemic and as an effort to empower the community through a participatory approach. This program aims to improve health literacy, social-religious capacity, and educational and economic empowerment in North Ampenan Village. The methods used were descriptive through observation, interviews, and documentation. The results show that health socialization, the production of natural hand sanitizers, fitness exercises, assistance with recitation and learning, maintenance of worship facilities, and facilitation of local tourism were able to increase health awareness, religious activities, literacy, and community involvement. Economic activities such as hydroponic assistance and tourism promotion also strengthened local potential. In conclusion, KKP-DR is effective as an adaptive community service model that integrates health, education, social, and economic fields. Scientifically, this activity emphasizes the importance of community service based on local needs and the strengthening of non-formal learning. Recommendations are directed at the sustainability of partnerships between universities and subdistricts as well as the development of community empowerment programs.